â€œEffect of Hyperglycemia on Electrolytes Imbalanceâ€ - Sharma, Anupriya (International Journal of Pharmaceutical & Biological Archive, 2011)
Electrolytes are the chemicals dissolved in the body fluid. The distribution has important consequences for the ultimate balance of fluids. The balance of the electrolytes in our bodies is essential for normal function of our cells and our organs. In present study a total of 33 hyperglycemic serum samples were analyzed for their electrolytes imbalance from their reference range corresponding to blood sugar value. At blood sugar level 130-190 mg % the percent variation value varied from 7.1 – 39.94 % and 18.25 – 66.28% For Na+ and K+ respectively. The Na+ ions not showed significance fluctuation from their normal range. At 190-250 mg % hyperglycemic range the level of various electrolytes showed significant variation from their reference range. The statistical analysis showed significant percent variation varies from 4 – 98% for Na + whereas 37 to 193% and6.5% - 97 % variation for K+ and Cl- respectively form their reference range. Higher range of sugar concentration (250 – 380 mg %) in blood serum, the Na+ concentration diverge from 10- 65%, K+ level speckled in the range of 14 – 80% and Cl- ions diverse 15-78 % . Sugar concentration in blood showed 54.51, Na+ 41.87, K+ 5.27 and Cl- 52.27 standard deviation respectively from reference range of concentration among all 33 samples. When data were subjected to Pearson Correlation analysis it was found that, There is a significant correlation of serum sodium (r = 0.107, P < 0.552), potassium (r = -0.035, P < 0.848), Chloride (r = 0.087, P < 0.631) with blood sugar. The present study concluded that the hyponatremia and hyperkalemia are more likely to be related to short-term metabolic control as reflected by blood glucose. Diabetes mellitus is associated with disturbances in electrolyte metabolism.